The Use of Temperaments in the Healing Process - Silvestri, Kenneth (Homœopathic Links, 2015)
Certain cases, if not all, necessitate a stereoscopic perspective. This perspective requires seeing simultaneous part to whole connections and variations to determining the desired results, all of which are geared to optimise the immune system. This article describes a systemic approach to homeopathic case taking that includes the use of the Genogram and Temperaments to assess the needed remedy through a process of joining with the subject's narrative, not as a passive ‘unprejudiced observer’.
Keywords: Temperaments; Genogram; Participant; Observer; Arsenicum album; Aurum metallicum; Bryonia alba; Ignatia amara; Natrum muriaticum; Natrum sulphuricum; Nitricum acidum; Phosphoricum acidum; Phosphorus; Staphysagria; Remedy differentiation